UPAYA MENINGKATKAN ORAL ACTIVITIES DAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS VII SMP NEGERI 1 SALAM MELALUI MODEL PROBLEM BASED LEARNING PADA TEMA PENCEMARAN AIR EFFORTS TO IMPROVE THE ORAL ACTIVITIES AND COGNITIVE LEARNING SCIENCE OUTCOMES THE STUDENTS OF CLASS VII SMPN 1 SALAM THROUGH THE MODEL OF THE PROBLEM BASED LEARNING ON THE THEME OF WATER POLLUTION - Zumi Hanifa; Zuhdan Kun Prasetyo; Susilowati Susilowati (Jurnal TPACK IPA, 2017)
Penelitian ini bertujuan untuk (1) mengetahui proses model Problem Based Learning dalam meningkatkan oral activities dan hasil belajar kognitif IPA siswa kelas VII SMP Negeri 1 Salam, Kabupaten Magelang, (2) mengetahui seberapa besar peningkatan oral activities dan hasil belajar kognitif siswa pada tema materi pencemaran air. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan menggunakanmodel Problem Based Learning. Instrumen yang digunakan berupa lembar observasi keterlaksanaan pembelajaran, tes hasil belajar kognitif, dan lembar observasi oral activities siswa. Kemampuan oral activities dianalisis menggunakan teknik persentase sedangkan hasil belajar kognitif IPA menggunakan gain score. Dari hasil analisis menggunakan teknik persentase diperoleh kenaikan oral activities siswa dengan kategori baik pada siklus I sebesar 26,47% (9 siswa), menjadi 61,76% (21 siswa) di siklus II. Besarnya peningkatan persentase oral activities siswa dari siklus I ke siklus II yaitu 35,29%. Pada analisis gain score untuk hasil belajar kognitif IPA siswa diperoleh hasil gain score siklus I sebesar 0.55 dan siklus II yaitu 0.62. Peningkatan gain score hasil belajar kognitif darisiklus I ke siklus II sebesar 0.07. Persentase ketuntasan hasil belajar kognitif IPA pada siklus I sebesar 82,36% (28 siswa) dan siklus II sebesar 85,29% (29 siswa).Kata kunci: Hasil Belajar Kognitif IPA, Model Problem Based Learning, Oral ActivitiesThis research aims to (1) know the process of the model of the Problem Based Learning in improving the oral activities and the results of cognitive learning science the students of class VII SMP 1 Salam, Magelang Regency, (2) know how big improvement of oral activities and the results of cognitive learning students on the theme of the material water pollution. The research method used is the Class Action Research (CAR) using the model of the Problem Based Learning. Instrument used in the form of observation sheet of learning implementation, test results of cognitive learning and observation sheet oral activities students. Oral ability activities were analyzed using the technique of percentage while the results of the cognitive learning science using gain score. The results of the study showed that the PBL model can improve the oral activities and the results of cognitive learning students. There are five steps in PBL teaching models that is giving the orientation about the problem to the students, organising students to examine, help independent investigation and groups to develop and present their artifact and exhibit, analyze and evaluate the process to resolve the issue. From the results of the analysis using the technique of the percentage obtained oral increase student activities with good category at cycle I of 26,47% (9 students), become 61,76% (21 students) in the cycle II. An increase in the percentage of oral activities students from I cycle to the cycle II namely 35,29%. On the analysis of the gain score for the results of cognitive learning science students obtained the results of score gains I cycle of 0.55 and the cycle II namely 0.62. Increased gain score results of cognitive learning from I cycle to the cycle II of 0.07. The percentage of learning in line with the results of the cognitive learning science at cycle I of 82,36% (28 students) and the cycle II of 85,29% (29 students).Keywords: Oral Activities, The Model of the Problem Based Learning, The Results of Cognitive Learning Science